Layout Strategy of Innovative Smart Grid System Integration Technology Development in Taiwan - Lin, Faa-Jeng; Chen, Yenhaw; Lu, Su-Ying; Tso, Chunto (International Journal of Energy Economics and Policy, 2020)
Taiwan government has promoted a policy of "Nuclear-free homeland” and increasing the proportion of green energy by 2025, it is expected that Taiwan will experience major energy and social transition. With the vigorous development of distributed renewable energy, Taiwan’s energy system will develop towards a multi-energy coexistence, distributed, and regionalized system. In the future, energy systems must integrate various types of power resources, be user-centered, and use information and communication technologies to integrate renewable energy, energy storage systems, smart meters and other devices. With optimal energy management, energy systems could improve energy conservation efficiency and reduce peak loads, and build a smart green energy system in a more efficient way. Refers to international experience in development trends of distributed power generation, demand response management, energy storage system and smart energy integration, this study develops and proposes the Layout Strategy of Innovative Smart Grid System Integration Technology Development in Taiwan. Keywords: Smart Grid, Innovative Integration Technology, Smart Energy JEL Classifications: L94, O31, Q42, Q48 DOI: https://doi.org/10.32479/ijeep.7484